Drought Index Determination Using the Batulayar Watershed Hydrology Model - Sri Rahayu Ayuba; Wilan Mooduto; Risman Jaya; Tisen Tisen; Ahmad Syamsurijal; Munajat Nursaputra (Newinera Publisher, 2022)
The Batulayar sub-watershed, also known as the Bongomeme sub-watershed, is one of the most important sub-watersheds in the Limboto watershed. Because there are oil palm and other plants in the Batulayar Sub-upstream watershed's area that cause drought and natural harm. The goal of this study was to assess the severity of the drought and develop a hydrological model for calculating the drought index in the Batulayar sub-upstream watershed's area. The mix approach was utilized, which combines Soil and Water Assessment Tool (SWAT) modeling with field survey methodologies. The study's findings suggest that land conversion in the Batulayar Sub-upstream watershed's area may have an impact on the watershed's function. The Batulayar Sub-SMDI watershed's value in the SWAT Model results shows that it ranges from -0.50 to -2.99 in March, April, May, November, and December over a 10-year period, and is classified as